Effect of Inspiratory Muscle Training on Maximal Inspiratory Pressure in Patients with Congestive Heart Failure (Global Journal of Medical Research, 2014)
Abstract not found
Keywords: Keywords: Congestive heart failure; Inspiratory muscles training; Maximal inspiratory pressure